T cells from chronic bone infection show reduced proliferation and a high proportion of CD28− CD4 T cells. (6th March 2014) - Kumar, G; Roger, P-M; Ticchioni, M; Trojani, C; Bernard de Dompsur, R; Bronsard, N; Carles, M; Bernard, E
Summary: Chronic bone infection is associated with bone resorption. From animal studies, CD3/CD28-activated T cells are known to enhance osteoclastogenesis and bone resorption. Because CD28 is expressed constitutively on T cells and its expression is down-regulated by chronic exposure to the inflammatory environment, we characterized co-stimulatory molecule expression on T cells from chronically infected patients. We used cytofluorometric techniques to phenotypically characterize T cells, its co-stimulatory molecules and perforin secretion from infected and non-infected human bones. Chronic bone infection was defined as infection lasting for more than a month. We show a higher T cell activation [human leucocyte antigen D-related (HLA-DR + )] in infected compared to non-infected bones: median being 16 versus 7%, P  = 0·009 for CD4 T cells, and 33 versus 15%, P  = 0·038 for CD8 T cells, respectively. However, T cell proliferation (Ki67 + ) was lower for CD8 T cells in infected bones: 26 versus 34%, P  = 0·045. In contrast, we detected no difference in apoptosis and regulatory T cells. In infected bone, we found higher CD28-negative CD4 + T cells compared to non-infected bone: 20 versus 8%, respectively ( P  = 0·005); this T cell subset had higher CD11b expression and perforin secretion. Chronically infected human bones are characterized by an increase of CD28-negative CD4 + T cells, indicating long-term activated cells with cytotoxic ability. Therefore, this alteration of co-stimulatory molecules may modify interactions with osteoclasts and impact bone resorption.